Helping hands or grabbing hands? An analysis of political connections and firm value - Chen, Carl R.; Li, Yingqi; Luo, Danglun; Zhang, Ting (Journal of Banking & Finance, 2017)
We construct a unique political connection index to capture variations in the strength of firm political relations in China. The index incorporates various channels through which a firm's executives, chairperson, directors, and other senior officers are politically connected with government officials and bureaucrats. Overall, there is a negative relation between our index and firm value for the full sample, but such negative relation mainly exists for state-owned enterprises (SOEs) and it becomes positive for non-SOEs. Furthermore, close examination shows an inverted U-shaped relation between political connections and firm value for the full sample in general and for non-SOEs in particular: Firm value increases initially at a lower level of connections and then begins to decrease at a higher level. The findings are consistent with the different business objectives and motivations of SOEs and non-SOEs in seeking political connections. Finally, our findings are robust after controlling for potential endogeneity and using an alternative headcount index construction method.